Discrimination, minority group endorsement and paranoia in adolescents: the moderating role of loneliness - Lyn Ellett; Katarina Krkovic; Brandon Gaudiano; Elizabeth Thompson; Jessica Kingston (International Journal of Adolescence and Youth, 2025)
Paranoid thoughts are relatively common in adolescents, but little is known about the factors that predict and attenuate paranoia in this group. The current study examined the effect of everyday discrimination, minority group endorsement and loneliness on paranoia in an international sample (n = 462) of adolescents from the UK and U.S.A. We tested a moderation model to determine (1) whether minority group endorsement and severity of discrimination independently predict paranoia; (2) if discrimination and minority group endorsement interact to predict paranoia; and, if so, (3) whether the impact of this interaction varies depending on level of loneliness. Regression analyses revealed everyday discrimination independently predicted paranoia. Minority group endorsement did not interact with discrimination as expected, and instead had a significant, independent effect on paranoia. Loneliness independently predicted paranoia and moderated the effect of discrimination on paranoia. The findings highlight the impact of adverse social contexts on paranoia in adolescents.